Kesenjangan Elektronics Human Resources Management Dalam Reformasi Birokrasi Di Kota Medan - Ilham, Amalia Rahmadani; Gusti, Ryndian; Dewi, Yupi Sasmita (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
The use of digital technology in ASN management is an important factor in the success of bureaucratic reform in public services. The application of E-HRM can improve employee performance but there are still gaps that occur in the Medan City Government related to user capabilities and user system design. The purpose of this study is to analyze evaluate and analyze the application of E-HRM in the bureaucratic transformation of Medan City. The dimensions used focus on aspects of bureaucratic transformation, administrative efficiency and ASN performance assessment. This research uses qualitative research methods through a literature study approach. Data collection is done through source identification using an academic data base. Data analysis techniques are thematic and interpretative through three stages, Open coding, Axial coding and narrative synthesis. The results showed that there are gaps in the implementation of E-HRM in Medan City. this is evidenced by the unpreparedness of infrastructure and employee literacy in using digital systems in ASN governance. The importance of bureaucratic reform must be supported by policies based on performance management approaches, independent supervision and sociotechnical in maintaining bureaucratic integrity.